Structure-Function Analysis of the Transmembrane Protein AmpG from Pseudomonas aeruginosa - Li, Peizhen (Public Library of Science, 2016)
AmpG is a transmembrane protein with permease activity that transports meuropeptide from the periplasm to the cytoplasm, which is essential for the induction of the ampC encoding β-lactamase. To obtain new insights into the relationship between AmpG structure and function, comparative genomics analysis, secondary and tertiary structure modeling, site-directed mutational analyses and genetic complementation experiments were performed in this study. AmpGs from different genera of bacteria (Escherichia coli, Vibrio cholerae and Acinetobacter baumannii) could complement AmpG function in Pseudomonas aeruginosa. The minimal inhibitory concentration (MIC) to ampicillin is 512 μg/ml for wild type strain PAO1, while it is 32 μg/ml for an ampG deletion mutant strain (PAO1ΔampG) with a corresponding decrease in the activity of the ampC-encoded β-lactamase. Site-directed mutagenesis of conserved AmpG residues (G29, A129, Q131 and A197) resulted in a loss of function, resulting in a loss of resistance to ampicillin in PAO1ΔampG. The G29A, G29V, A129T, A129V, A129D, A197S and A197D mutants had lower resistance to ampicillin and significantly decreased activity of the AmpC β-lactamase. The G29A, G29V, A129V, A197S and A197D mutants had decreased ampG mRNA transcript levels. The A129T and A129D mutants had normal ampG mRNA transcript levels, but the function of the protein was drastically reduced. Our experimental results demonstrate that the conserved amino acids played essential roles in maintaining the function of AmpG. Combined with the AmpG structural information, these critical amino acids can be targeted for the development of new anti-bacterial agents.